2001
DOI: 10.1002/1097-4628(20010509)80:6<841::aid-app1162>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Agitation effects in the semicontinuous emulsion polymerization of styrene and butyl acrylate

Abstract: The effect of agitation on the semicontinuous emulsion copolymerization of styrene and butyl acrylate was investigated. Both neat monomer addition and preemulsified feed were used. Experiments with and without a chain-transfer agent were carried out. For neat monomer addition, a mild degree of agitation (Ն 0.1 kW/m 3 ) was required to avoid monomer mass-transfer limitations, but even a moderate degree of agitation (0.3 kW/m 3 ) was not enough to overcome the CTA mass-transfer limitations. Agitation was much le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…[2][3][4][5] This has been associated with a formation of a larger number of particles. [6][7][8] The effects of impeller speed and/or type on the rate of copolymerisation, molecular weights, [4,9] and particle size distribution [10] have been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] This has been associated with a formation of a larger number of particles. [6][7][8] The effects of impeller speed and/or type on the rate of copolymerisation, molecular weights, [4,9] and particle size distribution [10] have been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…This is somewhat surprising as this CTA is rather water-insoluble and it has been reported that its mass transfer rate is affected by the agitation rate. [10,31] It is a matter of speculation if this was due to the presence of water soluble monomers which may change the character of the aqueous phase increasing the solubility of the CTA or to the high solids formulation which incremented the mass transfer by collision.…”
Section: Resultsmentioning
confidence: 76%
“…Emulsion polymerization depends on agitation in several ways. It determines the emulsification of the monomers, affects the transport of the reactants to the polymerization loci (polymer particles) and mixing time for sufficient homogenous distribution 13. It can also have an undesirable effect as it can promote coagulation 17, 51…”
Section: Resultsmentioning
confidence: 99%